Karakteristik Pasien Hipertensi di Puskesmas Sudiang Raya - Dahliah, Dahliah; Darwis, Nuari Aqriana; Azizah, Nur Zamzam (Indonesian Journal of Health, 2022)
Hypertension is one of the most common diseases found in primary medical practice. According to the NHLBI (National Heart, Lung and Blood Institution) 1 in 3 patients suffer from hypertension. Hypertension is also a risk factor for myocardial infarction, stroke, acute kidney failure and also death. The purpose of this study is to determine the characteristics of ARI patients in toddlers at the sudiang raya health center. description of the characteristics of hypertension in Puskesmas Sudiang Raya. Characteristics that are considered to consist of gender, age, and obesity. From 250 people it can be seen that the number of male patients with hypertension is 23 people (34.3%) and the number of female patients with hypertension is 44 people (65.7%). While the number of adolescent patients with age intervals of 12-16 years is 0 people (0%). The number of adult patients with age intervals of 26-45 years is 3 people (4.5%) and the number of elderly patients with an age interval> 45 years is 64 people (95.5%). While hypertension patients with normal BMI is 20 people (29.9%), overweight is 17 people (25.4%), obesity is 22 people (32.8%), and obesity II is 8 people (11 , 9)%). While the number of patients with normal hypertension (after routine care) is 9 people (13.4%), prehypertension is 31 people (46.3%), grade I of hypertension is 22 people (32.8%) and Patients with grade II of hypertension are free from 5 people (7.5%).